STUDI PENGARUH KRIB HULU TIPE IMPERMEABEL PADA GERUSAN DI BELOKAN SUNGAI (STUDI KASUS PERBANDINGAN ANTARA PANJANG KRIB 1/10, 1/5 DAN 1/3 LEBAR SUNGAI) - Paresa, Jeni (Faculty of Engineering, Musamus University, Merauke, Indonesia, 2016)
The research aimed to (1) examining the impact of the groin installation at the river upstream the scour reduction occuring at the river turn. (2) Determine the relationship between river flow, drainage and length of time in the crib impermeable upstream scour reduction that occurred in the bend of the river. The research was carried out by the experimental model examination in the laboratory with three discharge variation models (Q), three groin long variation i.e.:1/10, 1/5, and 1/3 from the river widht, and three flux time variations. The research results gained influence in the upper mounting groin can reduce scour that occurs at the bend of the river as seen from the volume of scour before installation and after installation of groin. The effect of time on volume and the influence of the length of scour groin to volume of scouring obtained from the graph that is most noticeable reduction in the minimum volume of scour occurs in groin with a length of 1/5 the width of the river.